From the City as Forest to Forest-City - Michele Caja (Agathón)
The relationship between city, architecture and nature dates back to the idea of city set up by the Enlightenment. A new idea of city surrounded by nature would had replace the compactness of the Baroque urban structure. From Laugier’s idea of city as a forest to the development of new urban prototypes represented within an idealized natural context, as in the drawings of Boullèe and Ledoux, emerges the search for new architectural and urban models alternative to the consolidated city. The contribution analyzes how this idea of city survived until modern times and how today seems to have come back to topicality in an attempt to re-naturalize the city.